Critical assessment of nursing profession in Saudi Arabia: With Reference to Work Environment - Abdulrahman ateah alzahrani, Mohammed Awadh AlJuaid, Ahmad Ayidh Al Salmi, Naif khdran althobite, Fahadabada LzIaz Alharthi (Journal of International Crisis and Risk Communication Research, 2024)
In case of developing countries like Saudi Arabia, the government and private hospitals are facing a certain shortage of nurses in terms of qualification and experience. Then there is another issue that the hospitals can engage only registered nurses and deploy them for patient care. This shortage is caused by many factors, including increased demand for health care due to advances in medical technology, population growth, increased life expectancy, and an increasing number of patients with serious and critical illnesses. This present study will focus on the work environment of nurses in the hospitals and healthcare organizations of the country. Study is based on primary data and ANOVA (One Way) is used for data analysis.